Stili alimentari e cibo biologico nelle scuole primarie Un'analisi sociologica a Rimini - Maturo, Antonio; Plava, Annalisa (Benessere Tecnologia Società, 2023)
This book brings together the results of a research focused on the quality and satisfaction on primary school canteens and, above all, on the impact they have on the eating habits of the children in Rimini and also their families. For many years, Rimini has been a virtuous city in the field of promoting healthy lifestyles, starting from primary school. Indeed, there are many acknowledgements obtained by Rimini school canteens for the quality of the food offered and its 'bio-respectability'. Rimini Municipality promotes the use of organic food in school canteens. A cutting-edge service that does not end at the moment of food consumption. Rimini's children present fewer eating disorders compared at the other children of the Emilia-Romagna area. Their well-being, therefore, is also analysed on the basis of 'secondary' effects such as the time of exposure to obesogenic factors that affect the future life course and the 'family space' which, through a socio-economic conditioning, affects opportunities for healthy growth. The results are encouraging, however it is crucial to maintain a high focus on this delicate and vulnerable period of life, in which it is necessary to create the context for healthy and virtuous choices that will release their effects throughout the child life.